Recurso educativo abierto y el aprendizaje basado en proyectos - Aguilar Chuncho, Valeria Estefania; Añazco Berru, Genesis Samanta (My University, 2023)
The objective of the work presented has as its main objective the application of an educational app in the subject of Language and Literature in order to strengthen the reading and writing of the students of the seventh year of Basic General Education of the School of Basic Education ¨Manuel Isaac Encalada Mora¨. With the realization of this work we have proposed to be able to share new forms of teaching, respectively using technology, the same that promotes a new vision, with new methodologies. Taking into account a methodological vision, this entire process is based on the creation of an application called ¨LectoApp¨ that has content such as language and culture, oral communication, reading, writing and evaluation that raises the integrated text of language and literature. seventh year. To obtain the respective results, two experiences were carried out, in the first experience we presented the application to the institution's teacher in person, where each of the activities proposed within the application was shown, in this case, the interface, the design, the colors and all the aspects that must be taken into account for the development of an application aimed at students In the second experience, the presentation of the application to the teacher in charge of the classroom and to the children of parallel seventh grade ̈A ̈ was already executed, explaining each of the particularities that LectoApp has after making the presentation of the application, we proceeded to carry out a survey to find out if the presented tool was liked by the students, where the results were successful, generating acceptance and a great impact when learning about the educational app. Highlighting the results of the students, we know that the subject of Language and Literature is considered difficult to learn due to the shortcomings that students have when writing or reading. The use of an educational app to strengthen literacy in students is suggested as an open educational resource. In this way, motivation and interaction in the classroom environment is promoted, which is what today is wanted to be achieved, allowing students to feel attracted and more active, creating new knowledge that meets the needs of students so that they learn differently.
El objetivo del trabajo presentado tiene como objetivo principal el aplicar app educativa en la asignatura de Lengua y Literatura como para fortalecer la lectoescritura los estudiantes de séptimo año de Educación General Básica de la Escuela de Educación Básica ¨Manuel Isaac Encalada Mora¨. Con la realización de este trabajo nos hemos propuesto el poder compartir nuevas formas de enseñanza, utilizando respectivamente la tecnología, la misma que promueva una nueva visión, con nuevas metodologías. Teniendo en cuenta una visión metodológica, todo este proceso está basado en la creación de una aplicación denominada ¨LectoApp¨ que tiene como contenidos como la lengua y cultura, la comunicación oral, lectura, escritura y evaluación que plantea el texto integrado de lengua y literatura de séptimo año. Para la obtención de los respectivos resultados, se realizaron dos experiencias, en la primera experiencia presentamos la aplicación a la docente de la institución de manera presencial, en donde se mostraron cada una de actividades planteadas dentro de la aplicación en este caso, la interfaz, el diseño, los colores y todos los aspectos que se deben tener en cuenta para el desarrollo de un aplicación dirigida para los estudiantes En la segunda experiencia ya se ejecutó la presentación de la aplicación a la docente encomendada del aula y a los niños de séptimo grado paralelo ̈A ̈, explicando cada una de las particularidades que tiene LectoApp luego de realizar la presentación de la aplicación, se procedió a realizar una encuesta para conocer si la herramienta presentada fue del agrado de los estudiantes, en donde los resultados fueron exitosos, generando la aceptación y un gran impacto al conocer la app educativa. Resaltando los resultados de los estudiantes sabemos que la asignatura de Lengua y Literatura se considera dificultoso aprender debido a las falencias que tienen los estudiantes al momento de escribir o de leer. Se sugiere como recurso educativo abierto la utilización de una app educativa para fortalecer la lectoescritura en los estudiantes. De esta manera se promueve la motivación e interacción en el entorno áulico que es lo que hoy en día se quiere lograr permitiendo que los estudiantes se sientan atraídos y más activos creando nuevos conocimientos que satisfacen las necesidades de los educandos para que si aprendan diferente.
Keywords: APLICACION; LECTOESCRITURA; FORTALECER; REA